2013
DOI: 10.1016/j.mcm.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Composite projection algorithms for the split feasibility problem

Abstract: a b s t r a c tThe split feasibility problem models inverse problems arising from phase retrieval problems and the intensity modulated radiation therapy. In this paper, two methods have been presented for solving the split feasibility problem. The strong convergence results of presented algorithms have been obtained under some mild conditions. Especially, the minimum norm solution of the split feasibility problem can be found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It is well-known that split feasibility problem (in short, SFP) is a model of several problems, namely, sensor network, radiation therapy treatment planning, resolution enhancement, wavelet-based denoising, antenna design, computerized tomography, materials sciences, watermarking, data compression, magnetic resonance imaging, color imaging, optics and neural networks, graph matching, adaptive filtering, image recovery; See, for example, [1,7,11,12,15] and the references therein. During the last decade, a large number of algorithms have been proposed for solving SFP under the nonemptyness of the solution set of SFP; See, for example, [1,7,[9][10][11][12]15,26,33,34,36] and references therein.…”
Section: Application To Split Feasibility Problemsmentioning
confidence: 99%
“…It is well-known that split feasibility problem (in short, SFP) is a model of several problems, namely, sensor network, radiation therapy treatment planning, resolution enhancement, wavelet-based denoising, antenna design, computerized tomography, materials sciences, watermarking, data compression, magnetic resonance imaging, color imaging, optics and neural networks, graph matching, adaptive filtering, image recovery; See, for example, [1,7,11,12,15] and the references therein. During the last decade, a large number of algorithms have been proposed for solving SFP under the nonemptyness of the solution set of SFP; See, for example, [1,7,[9][10][11][12]15,26,33,34,36] and references therein.…”
Section: Application To Split Feasibility Problemsmentioning
confidence: 99%
“…where F(U) and F(T) mean the fixed point sets. If U and T are both metric projects, problem (1) is actually problem (2) [13,14], and further development of this topic made by [15][16][17][18][19]. To be more specific, given two nonempty closed convex sets C ⊂ H 1 and Q ⊂ H 2 and A is above mentioned.…”
Section: Introductionmentioning
confidence: 99%
“…In [7,9,10], it has been shown that the SPF (1.1) can also be used to model the intensity-modulated radiation therapy. Various iterative algorithms have been studied to solve the SFP (1.1), see, e.g., [8,14,16,18,22,25,27,[30][31][32] and the references therein. In particular, Jung [16] introduced iterative algorithms based on the Yamada's hybrid steepest descent method [28] for solving SFP (1.1).…”
Section: Introductionmentioning
confidence: 99%